Saying Goodbye: Military Deployments - Alexandra Ulrich; Suzanna Smith (EDIS)
“Those last few hugs, the last few kisses, the last few goodbyes are what many military families across the United States have experienced when seeing a loved one leave for deployment. An estimated 1.4 million servicemen and women serve as active duty members in the Army, Navy, Marine Corps, or Air Force. Deployments are nothing new in the military community. However, during these times of separation, family members of those serving, especially the children, undergo many hardships. Studies show children’s reactions to separation can even lead to depression.” This 2-page Family Album Radio transcript was written by Alexandra Ulrich and Suzanna Smith, and published by the UF Department of Family, Youth and Community Sciences, November 2012.